Fiji Trade Facilitation Challenges for Women Traders and Freight Forwarders : Survey Findings and Recommendations - World Bank (World Bank, Washington, DC, 2021)
This note presents the results of a survey undertaken in Fiji from May to June 2019 with the intention to identify the specific challenges men and women cross-border traders are facing related to trade facilitation at the firm level. Generally, efforts to improve trade conditions, especially relating to women cross-border traders, have been progressing over the years. Yet, there is limited work focusing on trade facilitation initiatives and trade competitiveness interventions aimed at women firms who face trading barriers that are not strictly linked to tariffs or policies. There is a global data gap on the nature of barriers that women traders face related to trade facilitation at the firm level. In fact, the problem is even deeper rooted; there is a global vacuum of knowledge about the exact proportion of cross-border traders that are women. No country, not even the gender equality champions in Northern Europe, can easily confirm the number of women that undertake cross-border trade in their respective countries. A survey designed to collect data on these challenges is being rolled out in the Pacific. Countries in the Pacific Islands region face unique development challenges: they are physically detached from major markets, have small populations spread across many islands and time zones, confront the worst impacts of climate change, and are some of the most vulnerable countries to natural disasters in the world.